2014
DOI: 10.1111/bcpt.12280
|View full text |Cite
|
Sign up to set email alerts
|

Inosine Strongly Enhances Proliferation of Human C32 Melanoma Cells through PLCPKCMEK1/2‐ERK1/2 and PI3K Pathways

Abstract: Malignant melanoma is the most deadly type of skin cancer. The lack of effective pharmacological approaches for this tumour can be related to the incomplete understanding of the pathophysiological mechanisms involved in melanoma cell proliferation. Adenosine has growth-promoting and growth inhibitory effects on tumour cells. We aimed to investigate effects of adenosine and its metabolic product, inosine, on human C32 melanoma cells and the signalling pathways involved. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…We could only verify the stimulating capacity of adenosine in our system, and it seems to be limited by the concentration of the adenosine vehicle ammonia. It has already been reported that inosine, and not adenosine, exerts potent proliferation-stimulatory actions on melanoma cells, mainly through the engagement of A3 adenosine receptor (40). Since we have not inhibited the catabolism of adenosine to inosine in the SNs, it is likely that the stimulation of proliferation of melanoma cells is ultimately supported by inosine.…”
Section: Discussionmentioning
confidence: 99%
“…We could only verify the stimulating capacity of adenosine in our system, and it seems to be limited by the concentration of the adenosine vehicle ammonia. It has already been reported that inosine, and not adenosine, exerts potent proliferation-stimulatory actions on melanoma cells, mainly through the engagement of A3 adenosine receptor (40). Since we have not inhibited the catabolism of adenosine to inosine in the SNs, it is likely that the stimulation of proliferation of melanoma cells is ultimately supported by inosine.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the A3R agonists CL-IBMECA and CF102 have shown promise in vitro by inducing apoptosis in multiple tumor types through the suppression of PKA, ERK and AKT pathways [80,[97][98][99]. Conversely, it has also been reported that inosine-mediated activation of the A3R can enhance melanoma cell proliferation through activation of the ERK pathway [100] and a cytoprotective role for the A3R has also been described [101]. Similarly, activation of the A3R has been suggested to enhance the migration or invasion of tumor cells [73,102,103].…”
Section: Expression Of Adenosine Receptors and Signaling Pathways In mentioning
confidence: 99%
“…Hence, PKC enzymes play important roles in several signal transduction cascades. Soares et al [26] proposed that the simultaneous activation of the phospholipase C (PLC)-PKC-MEK1/2-ERK1/2 and phosphatidylinositol-3-kinase (PI3K) pathways is the principal mechanism responsible for the proliferative effect elicited by inosine and its significant role in melanoma cancer progression. Moreover, Halder et al [27] observed a marked variation in the expression of PKCα and PKCδ isotypes in B16F10 melanoma tumor cells compared with normal melanocytes and suggested the presence of a reciprocal PKC signaling pathway.…”
Section: Discussionmentioning
confidence: 99%